Getting Married is a Simple Matter: Early Marriage among Indonesian Muslim Girls in Rural Areas of Java - Setiadi Setiadi (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2021)
The high rate of child marriage has become a global community concern, including in Indonesia as the world's biggest Muslim country. This study explores the views and experiences of Muslim girls and local actors of early marriage in rural areas of Java, Indonesia. Applying the qualitative research method and case study approach, this research is performed in a hamlet on mount Sumbing. This study concluded that young-women marriage is still considered as normal and acceptable from a socio-cultural perspective. For the local community, marrying their child at a very young age will guarantee labour availability, psychological security in old age and strengthen family bonds. The seriousness of life's challenges towards adulthood leads marriage at a young age to become a choice of socio-psychological coping mechanisms idealized by some young women. This phenomenon is also influenced by the existing local socio-cultural values that place marriage as a solution to socio-economic, socio-cultural problems and guarantee future generations' continuity.